Fatal Postpartum Hemorrhage in a Patient with Niemann-Pick Disease Type B - Atakan Tanacan; Abdullah Yalcin; Canan Unal; Seda Banu Akinci; Mehmet Sinan Beksac (Case Reports in Obstetrics and Gynecology)
Background. Niemann-Pick Disease Type B (NPD B) is a rare lysosomal storage disorder resulting from an inherited deficiency of acid sphingomyelinase activity. Here, we report the case of a splenectomized patient with NPD B who died because of severe postpartum hemorrhage (PPH). Case Presentation. A 23-year-old nulliparous woman was admitted to intensive care unit (ICU) after cardiopulmonary arrest during urgent hysterectomy because of severe postpartum bleeding. The patient concealed her disease from her family and obstetricians during her pregnancy, and her NPD B diagnosis was revealed during her stay in ICU while searching for the cause of the splenectomy and severe bleeding. Unfortunately, she had a detrimental course with hypoxic brain injury leading to brain death. Conclusions. In conclusion, physicians should keep in mind that patients with a history of splenectomy and/or uncontrollable hemorrhage must be carefully evaluated for rare diseases like lysosomal storage diseases and that NPD B can cause mortality because of postpartum bleeding. Adult intensivists should be familiar with adult presentations of rare metabolic or genetic diseases as more and more children with metabolic or genetic diseases will survive to adulthood and will be admitted to and unfortunately will even die in the adult ICU.